Smoking Among Dental Students - Abdulwahhab, Nagwan Ali; Rayan Waseem Waleed; Aya Hamid Mahdi; Jehan Yawez Al-Demirchi; Zahraa Ahmed Abdulwahid (Universitas Muhammadiyah Sidoarjo, 2025)
Tobacco use remains one of the leading causes of preventable morbidity and mortality worldwide, contributing to millions of deaths annually. Dental students, as future healthcare providers, play a crucial role in tobacco prevention and cessation; however, high smoking prevalence among them raises concern about their readiness to serve as health advocates. Despite global research, little is known about the prevalence, patterns, and determinants of smoking among dental students in Iraq, particularly regarding their knowledge and attitudes toward cessation. This study aimed to investigate the prevalence of tobacco use, identify associated risk factors, and evaluate dental students’ knowledge and attitudes toward smoking and cessation. A cross-sectional survey of 250 students revealed a smoking prevalence of 37%, with a significant gender disparity (36% among males vs. 1% among females). Cigarettes (66%) and shisha (62%) were the most commonly used tobacco products. Stress (55%) and enjoyment (55%) were the leading reasons for smoking initiation, followed by addiction (28%) and peer pressure (14%). No significant reduction in smoking rates was observed with increasing age or academic level. Two-thirds of students reported that the dental curriculum inadequately addressed smoking cessation. This is among the first studies to systematically assess smoking behavior and cessation knowledge among Iraqi dental students, highlighting gaps in education. The findings emphasize the urgent need to integrate comprehensive tobacco education and cessation training into dental curricula to empower students as effective public health advocates. Highlights: Smoking prevalence among dental students reached 37%, with a stark gender difference (36% males vs. 1% females). Cigarettes (66%) and shisha (62%) were the most commonly used tobacco products. Stress and enjoyment were the main reasons for smoking initiation (55% each), while two-thirds of students felt their curriculum lacked adequate smoking cessation education.